Effect of damping distribution on coupling in panel–cavity systems: Conditions for optimality through a modal approach. (1st December 2020) - Nerse, Can; Wang, Semyung; Goo, Seongyeol
Highlights: Nonproportionally damped panel– cavity systems are studied. The coupling formulation is expressed with complex modal analysis. A nongradient based topology optimization of a damping layer is conducted. The coupling parameters are shown to correlate with the optimal damping layout. The numerical results are discussed with physical and practical implications. Abstract: In this study, we examine an acoustic–structure interaction problem for nonproportionally damped systems. Coupled responses for a structure and acoustic enclosure are derived using a modified modal coupling formulation. Uncoupled modal patterns are used to assess the coupling effectiveness. Comparison with a proportional damping case reveals characteristics that associate complex modes with damping optimality. Such an interrelation is investigated through topology optimization of a damping layer to minimize the acoustic pressure in the cavity. The findings of this numerical study indicate a spatial relation between the imaginary part of the coupling coefficient and the optimal damping layout. Further investigation of complex modal patterns with wave interpretation shows that the optimal damping characteristics of the panel can be expressed by a spatially varying nonproportional damping index. Case studies involving various nonproportional damping configurations are presented to confirm the significant correlation with respect to observed phenomena. Graphical abstract: Image, graphical abstract